The Greek presence in the ancient Maghreb between the fiction of the novel and the reality of colonial motives - Serhane , nadjat; RAHMANI, Belkacem (The Algerian Historical Journal, 2026)
During the seventh century BC, the ancient Maghreb witnessed an expansionist movement and colonial activity on its lands. By the Greeks. Based on that, our article came to investigate the real motives that were behind this expansion, as we recorded two types of motives. The first was a mythological one that was linked to the gods and was used as an excuse to give legitimacy to the colonization of the region. The second is real, embodied in the driving reasons for the Greek colonial presence in North Africa. There were many political, economic, and social reasons.